2012
DOI: 10.1002/aic.13755
|View full text |Cite
|
Sign up to set email alerts
|

A study of liquid droplet disintegration for the development of nanostructured coatings

Abstract: Thermal spray coatings produced from a liquid feedstock are receiving an increasing level of interest due to the advanced, nanostructured coatings which are obtainable by these processes. In this article, a high‐velocity oxy‐fuel (HVOF) thermal spray system is computationally investigated to make a scientific assessment of the liquid droplet behavior on injection. An existing liquid‐fuelled HVOF thermal spray gun is simulated using the computational fluid dynamic approach. The steady‐state gas‐phase dynamics a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 52 publications
0
27
0
Order By: Relevance
“…The Discrete Phase Model (DPM) treated the liquid droplets in Lagrangian manner and tracked the droplets throughout their flight. The TAB and DPM models are well adapted to the conditions of spraying and validated in the earlier studies; details can be found in [20,50,51,64].…”
Section: Secondary Breakup Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…The Discrete Phase Model (DPM) treated the liquid droplets in Lagrangian manner and tracked the droplets throughout their flight. The TAB and DPM models are well adapted to the conditions of spraying and validated in the earlier studies; details can be found in [20,50,51,64].…”
Section: Secondary Breakup Modelmentioning
confidence: 99%
“…The hydrodynamic force required for the deformation of droplets is related to the surface tension force acting to retain the droplet form by We. Since the Ohnesorge number (Oh) remains below 0.1 (Oh ≪ 0.1) in the computational domain, the main parameter related to breakup physics is the We [20,64,65]. The Discrete Phase Model (DPM) treated the liquid droplets in Lagrangian manner and tracked the droplets throughout their flight.…”
Section: Secondary Breakup Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…They also concluded that the aqueous solution has a larger influence on the gas dynamics, in contrast to the organic solvent that has less impact on the gas velocity and temperature. Tabbara and Gu [282] modeled the water droplet injection into a liquid-fueled HVOF torch (JP5000). Liquid kerosene and oxygen were axially injected into the combustion chamber while water droplets were injected into the barrel radially.…”
Section: Literature Review On Hvsfs Modelingmentioning
confidence: 99%